Notes on the liability derived from wrongful dismissal or dismissal conducted in bad faith within the Peruvian legal system: the rhetoric of punitive damages and the denaturalization of lucrum cessans - Campos García, Héctor (2019)
The peruvian Supreme Court has considered at the V Labour Plenary that the remunerations left to be received in cases of uncaused or fraudulent dismissal have a compensatory nature. This interpretation has led the notion of punitive damages to be used rhetorically and has provoced that differentiated rules are established without justification in relation to void dismissal.The article explains the reasons why the Supreme Court assumed such position and criticizes those reasons. Finally, a possible solution is presented so that the magistrates do not apply the refered interpretarion in specific cases.